Modeling commodity markets in stochastic contexts: A practical guide using the RECS toolbox version 0.5 - Gouel, Christophe (International Food Policy Research Institute, 2012)
This document describes the RECS toolbox and also several applications of this modeling framework to commodity markets related issues. It assumes basic knowledge of Matlab, and of dynamic economic models (see Adda and Cooper, 2003, for an introduction). Storage models are presented in brief; for more information please refer to the original papers or to Williams and Wright (1991), which provide detailed descriptions of many of these models.